IS ADVANCED MATERNAL AGE INDEPENDENT RISK FACTOR FOR MATERNAL-PERINATAL COMPLICATIONS? - Tipiani Rodríguez, Oswaldo (2015)
Objective: To determine whether maternal age 35 years or older is an independent risk factor for maternal and perinatal complications. Design: Case-control, comparative study. Setting: Arzobispo Loayza National Hospital, Lima, Peru, III level teaching hospital. Participants: One hundred and sixty six 35 years or older pregnant women were compared with 324 pregnant women less than 35 years old. These patients were randomly selected of those attended in 2005. Mantel-Haenszel x2 statistics was used to compare age specifically, with P< ,05 considered statistically significant. Main outcome measures: Multiple logistic regression analysis was used to evaluate the association between maternal age and outcome variables, controlling for possible confounding factors. Results: Advanced maternal age was independently associated with abnormal fetal presentation during labor (OR 1,05; 95% IC 1,01, 1,10), cesarean section due to third trimester bleeding (OR 1,05; 95% IC 1,01, 1,09), preterm delivery (OR 1,08; 95% IC 1,02, 1,14), chronic hypertension (OR 1,03; 95% IC 1,01, 1,05), recurrent abortion (OR 3,09; 95% IC 1,49, 6,43), and grand multiparty (OR 10,34; 95% IC 3,46, 30,93). The prevalence of gestational diabetes was higher in the cases. Perinatal mortality rate, 7 or lower 5-minute Apgar score, low-birth-weight and puerperal morbidity were not influenced by maternal age. Conclusions: After correcting for confounding factors the advanced maternal age represented an independent risk factor for medical and obstetric complications. The recognition of such factors is important for the reduction of perinatal morbidity and mortality in this group of patients.